Repeated snowball–hothouse cycles within the Neoproterozoic Sturtian glaciation - Charlotte Minsky; Robin Wordsworth; David T. Johnston; Andrew H. Knoll (Proceedings of the National Academy of Sciences, 2026)
The Neoproterozoic Era was a pivotal era of Earth’s history in which multiple severe glaciations profoundly influenced the biosphere, but explaining the duration and nature of these events remains a major challenge. Notably, geochronology indicates that the Sturtian glaciation lasted for ∼56 Myr—far longer than can be accommodated by canonical “Snowball” or “Slushball” models. Here we use a coupled box model of the Neoproterozoic climate and carbon cycle to develop a hypothesis for Sturtian climate evolution. We show that weathering of the Franklin igneous province would have caused Earth to enter a limit cycle regime, alternating between Snowball and hothouse states for the duration of the Sturtian. This scenario resolves the duration problem, is allowable given currently observed patterns of sedimentation, and predicts syn-Sturtian oxygen stability.